Decolonialism - Legg, Stephen (Wiley, 2017)
This piece opens with some reflections on the geographies of postcolonial scholarship and encourages us to trace out colonial durations in our lives and in the provocations we face. Two examples are given, from the International Conference of Critical Geographers and the Nottingham Citizens’ Hate Crime Commission, before reflecting on ‘decolonialism’ might mean for geography.